2021
DOI: 10.3390/ijerph18052677
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Weight: Connecting Exoskeleton Effectiveness with Ergonomic Risk during Manual Material Handling

Abstract: Occupational exoskeletons are becoming a concrete solution to mitigate work-related musculoskeletal disorders associated with manual material handling activities. The rationale behind this study is to search for common ground for exoskeleton evaluators to engage in dialogue with corporate Health & Safety professionals while integrating exoskeletons with their workers. This study suggests an innovative interpretation of the effect of a lower-back assistive exoskeleton and related performances that are built… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 76 publications
4
27
0
Order By: Relevance
“…For instance, Lamers et al (2020) evaluated assistance benefits of a soft, passive-elastic back exo using two separate analyses -EMG, and a physics-based moment balance -and found the magnitude of back offloading estimated by each analysis to be similar. Likewise, a study on a rigid robotic back exo (Di Natali et al, 2021) found EMG and physics-based analyses yielded similar results in terms of reductions in back loading during lifting. In both studies, the physics-based analysis predicted slightly less back offloading than the EMG-based analysis, suggesting it may provide slightly more conservative estimates of exo benefits.…”
Section: Exo-lifft For Ergonomic Assessment Of Back Injury Risk and Damage While Wearing Exosmentioning
confidence: 74%
See 4 more Smart Citations
“…For instance, Lamers et al (2020) evaluated assistance benefits of a soft, passive-elastic back exo using two separate analyses -EMG, and a physics-based moment balance -and found the magnitude of back offloading estimated by each analysis to be similar. Likewise, a study on a rigid robotic back exo (Di Natali et al, 2021) found EMG and physics-based analyses yielded similar results in terms of reductions in back loading during lifting. In both studies, the physics-based analysis predicted slightly less back offloading than the EMG-based analysis, suggesting it may provide slightly more conservative estimates of exo benefits.…”
Section: Exo-lifft For Ergonomic Assessment Of Back Injury Risk and Damage While Wearing Exosmentioning
confidence: 74%
“…LiFFT is based on fatigue failure processes, which underly how microdamage within materials (including biological tissues) accumulates during repeated loading cycles. Fatigue failure underlies both the etiology of overexertion injuries (Edwards, 2018;Gallagher and Heberger, 2013;, and the biomechanical rationale for why/how exos are expected to reduce injury risks (Abdoli-Eramaki et al, 2007;Di Natali et al, 2021;Lamers et al, 2018), which is why this tool has the potential to unify ergonomic assessment and exo assistance. Here we describe how LiFFT can be adapted to assess injury risk when wearing back exos and share examples of various uses.…”
Section: Ergonomic Need and Proposed Solution For An Exo-compatible Risk Assessment Tool For The Backmentioning
confidence: 99%
See 3 more Smart Citations